EDUKASI KEPADA SISWI SMK PELITA ALAM TERKAIT MENGENAL STRUKTUR DAN SISTEM REPRODUKSI PADA WANITA SERTA PENTINGNYA MENJAGA KESEHATAN REPRODUKSI - Herty Nur Tanty; Vidia Anwar; Farida Tuahuns (Jurnal Pengabdian IKIFA, 2025)
Adolescent girls' knowledge regarding reproductive health tends to be lacking, indicating that they do not know and understand the importance of reproductive health. Lack of understanding regarding the reproductive system causes young women to be unaware of their own bodies and not know how to care for them. The aim of this service activity is to provide education to Pelita Alam Vocational School students regarding the introduction of the reproductive system and the importance of maintaining reproductive health through interactive lectures and discussions. This service activity was carried out on May 21, 2024, and was attended by 23 class XI and XII female students. The increase in respondents' knowledge was measured using pretest and posttest questionnaires. The results of data processing show an increase in posttest scores compared to the pretest. Additionally, during interactive discussion activities, respondents were seen to be active in asking questions. It can be concluded that this service activity was quite successful based on the initial objectives.